Primary Care of the Solid Organ Transplant Recipient - Wong, Christopher J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Solid organ transplantation offers a new chance at life to those suffering from failing organs. With these successes, however, comes the everyday management that is required to maintain health. The field of solid organ transplantation has become a part of medicine that generalists should be familiar with, as recipients are living longer and frequently returning to primary care for management. While specialists will still need to be involved with the care of solid organ transplant recipients on a life-long basis, many conditions will still need initial and often ongoing care by generalists, including infections, metabolic conditions, psychiatric illnesses, and malignancy. This book focuses on the care of adult solid organ transplant recipients, and is targeted at the level of the primary care provider. It begins with an introduction and overviews of solid organ transplantation and anti-rejection medications. It then delves into organ-specific chapters that provide the primary care provider with an overview of how to take care of patients with the most commonly-transplanted solid organs: kidney, kidney-pancreas, liver, heart, and lung. The final section focuses on specific complications that arise from transplantation including cancer, metabolic conditions, infections, and common presenting syndromes. Preventative health is also discussed, and the book concludes with a chapter on palliative care. Primary Care of the Solid Organ Transplant Recipient is a unique text that provides the reader with organ and complication-specific sections that can be independently read as they relate to the individual physicians and their patients. Written by experts in the field, this text is a valuable resource for primary care providers, medical students, residents and anyone involved in the care of solid organ transplant recipients. .
introduction -- Overview of Adult Solid Organ Transplantation for Primary Care Providers -- Anti-Rejection Medication Therapy in the Adult Solid Organ Transplant Recipient -- Primary Care of the Adult Kidney Transplant and Kidney-Pancreas Transplant Recipient -- Primary Care of the Adult Liver Transplant Recipient -- Primary Care of the Adult Heart Transplant Recipient -- Primary Care of the Adult Lung Transplant Recipient -- Infections in the adult-solid organ transplant recipient -- common syndromes in the adult solid organ transplant recipient -- cancer risk in the adult solid organ transplant recipient -- metabolic complications in the adult solid organ transplant recipient -- preventive health in the adult solid organ transplant recipient -- palliative care in the adult solid organ transplant recipient.
Keywords: Primary care (Medicine).; General practice (Medicine).; Primary Care Medicine; General Practice / Family Medicine